Modern Research with Bryophytes: An Overview - N. G. Miller (Memoirs of the Torrey Botanical Club, 1993)
The idea that bryophytes form a truly ancient lineage of plants rests upon inadequate fossil evidence of their presumed lower Paleozoic origins from Charalean-like or Coleochaetalean-like algae. In this regard a special challenge is the unequivocal interpretation of the biphasic life cycle of bryophyte-like plant fossils. Unique among land plants in having a dominant gametophyte phase, bryophytes present opportunities for a broad array of research not readily undertaken in sporophyte-dominated organisms. This is enhanced by the ease with which bryophytes in culture can be manipulated experimentally and subjected to analytical testing. Such attributes have permitted numerous recent advances in what is known about the cell biology and physiology of this group of plants. Progress is also evident in deciphering the natural products chemistry of bryophytes. Of far reaching importance are recent advancements in understanding speciation and genetic diversity within species. Where bryophytes are vegetation dominants (e.g., polar, arctic, and boreal regions, and low latitude-high elevation forests), the importance of research involving these organisms will increase in proportion to environmental pressures created by the expanding human population and its agricultural and industrial base.
Keywords: bryophyte epiphytes; fossil phytodebris; land plant fossils; molecular systematics; moss banks